Advanced cardiac imaging in preventing sudden cardiac death in athletes - Locatelli, E.; Lisi, C.; Monti, L.; Catapano, F.; Francone, M. (Journal of the Mexican Federation of Radiology and Imaging, 2023)
Competitive athletes are known to undergo physiological adaptations to meet the demands of rigorous training which can mimic pathological conditions, leading to an overlap between normal physiological changes and potentially life-threatening cardiac abnormalities. Sudden cardiac death (SCD) in athletes is a rare but devastating event, underscoring the need for early detection of cardiac abnormalities to prevent such tragedies. This review highlights the pivotal role of advanced cardiac imaging techniques, specifically cardiac magnetic resonance imaging (CMR) and coronary computed tomography angiography (CCTA), in the prevention of SCD in competitive athletes. CMR and CCTA offer non-invasive, comprehensive assessments of cardiac morphology and function, providing valuable insights into the athlete`s heart. Various physiological adaptations observed in athletes` hearts will be presented, including left ventricular hypertrophy and right ventricular dilation, which can be mistaken for pathological conditions. The "grey zone" concept underscores the importance of advanced imaging in distinguishing between normal and potentially abnormal cardiac changes. For specific pathological conditions linked to SCD in athletes, CMR aids in accurate diagnosis by differentiating tissue characteristics and assessing late gadolinium enhancement (LGE) patterns. Additionally, CMR plays a critical role in identifying coronary artery anomalies, myocarditis, and coronary artery disease in athletes over 35 years old, enabling early intervention and treatment. The new Padua criteria will also be discussed, which incorporate tissue characterization and novel ECG criteria to diagnose arrhythmogenic cardiomyopathy more accurately. Collaborative efforts between sports medicine specialists, cardiologists, and radiologists are essential in establishing standardized protocols for responsible imaging use, ultimately enhancing the safety and well-being of competitive athletes.